Monetary policy and currency (non) neutrality: A comparative analysis between the Austrian, Post-Keynesian, New-Classical and New-Keynesian - Santana, Bernardo (2021)
The purpose of this article is to clarify the relationship between the different views of the following schools: Austrian, Post-Keynesian; New-Classical; and New-Keynesian on the impact of currency on the economy and monetary policy recommendations. The theoretical framework addresses these four schools and allows us to understand their perceptions regarding the neutrality or non-neutrality of money. Differences in perceptions are linked to recommendations or rejections of governmental interference through monetary policies. These perceptions are presented, comparing the long-term effects of monetary expansion according to each school. The role of the Central Bank as a stimulating economic agent according to each school is discussed. Treating money as neutral or non-neutral does not mean having the same view about its economic system impacts. Each school has its hypotheses and a specific and differentiated understanding of currency manipulation consequences through government interventions via accommodative monetary policies. A clear view of money and its role is essential to avoid misguided government policies that at times can aggravate or create more problems than solutions. It is qualitative research with explanatory scope based on a bibliographic survey.